Implementasi Merdeka Belajar dalam Peningkatan Literasi dan Numerasi Siswa (Indo-MathEdu Intellectuals Journal, 2023)
This study evaluates the effectiveness of the "Merdeka Belajar" program launched by the Indonesian Ministry of Education and Culture in improving students' literacy and numeracy. A quantitative method with a quasi-experimental design was used to compare literacy and numeracy scores before and after program implementation in 10 senior high schools in East Java Province, with a total of 100 students as samples. The results showed significant improvements in literacy scores from 62.5 to 75.3 and numeracy scores from 58.7 to 72.1, with a p-value